The long haul - Bakshi, Rajni (Bombay : BUILD Documentation Centre, 1986)
Publisher's preface: The strike by the textile workers of Bombay (1982-?) was a momentous event. Its significance for the working class movement has perhaps not yet been adequately understood. This is in any way no simple task. The question will be debated by experts in analysis and action for quite some time. A contribution towards this process is a compila-tion of facts about the strike. Rajni Bakshi in this book presents the facts. Based on interviews, dis-cussions and secondary sources she reconstructs the events as they took place and attempts to get at the forces and factors that lay behind the events. There would be no uniform agreement about her interpretations and conclusions. There would how-ever not be, we hope, any dispute over the facts and hence the book can become a basis for dis-cussion. It is only fair to add that the views expressed are of the author and do not reflect the opinions of BUILD Documentation Centre.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Textile Workers' Strike, Mumbai, India, 1982-1983.